General Objectives of Teaching Students Using Modern Methods in Pedagogy - Islikov Sayid Khalilovich (Peerian Journals Publishing, 2022)
Pedagogy is the study of teaching techniques, including educational objectives and strategies for achieving them. The discipline mainly draws on educational psychology, which incorporates empirical learning theories, and, to a lesser extent, on education philosophy, which examines the purposes and worth of education from a philosophical standpoint. The teacher and the student collaborate on a program (the subject) that is intended to change the students' experiences and understanding in some way during the teaching process. The general goals of instructing pupils using contemporary pedagogical techniques are covered in this article.
Keywords: Pedagogical techniques; general goal; methods; media